2018
DOI: 10.1039/c8ra00820e
|View full text |Cite
|
Sign up to set email alerts
|

An antibiotic agent pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro isolated from a marine bacteria Bacillus tequilensis MSI45 effectively controls multi-drug resistant Staphylococcus aureus

Abstract: A new antibiotic agent from sponge associated marine bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 41 publications
2
45
0
2
Order By: Relevance
“…Furthermore, the isolated compound was non-cytotoxic towards mouse embryo fibroblast and non-haemolytic. Hence, compound (5) was recommended as an interesting compound that warrants further study considering its safety, non-haemolytic property as well as having dual role of reducing oxidative stress and inhibiting multidrug-resistant Staphylococcus aureus strains [87].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the isolated compound was non-cytotoxic towards mouse embryo fibroblast and non-haemolytic. Hence, compound (5) was recommended as an interesting compound that warrants further study considering its safety, non-haemolytic property as well as having dual role of reducing oxidative stress and inhibiting multidrug-resistant Staphylococcus aureus strains [87].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, GC-MS was used in the present study to detect chemical constituents in the methanolic extract MUSC 5 (Table 4 and Pyrrolopyrazines exist as a class of heterocyclic compounds frequently recovered from microbial extracts. For example, compound (1) isolated from a Bacillus strain was identified as the active compound with strong DPPH radical scavenging activity as well as exhibiting activity against multi-drug resistant Staphylococcus aureus [82] .Compound (2) among the 3 constituents present in ethyl acetate extract was identified in a marine Streptomyces sp. S2A as the major constituent responsible for the antioxidant activities (DPPH, ABTS, metal chelating and FRAP), antibacterial, enzyme inhibitory and cytotoxic effects [83] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed bioactivity from bioactive compound: 1-Naphthylbut-1-yn-3-one, Neophytadiene, 3-benzyl-1,4-diaza-2,5-dioxobicyclo, 13-Docosenamide, Stigmast-5-en-3-ol, I-nonadecene , oleic acid amide (Chajjed et al 2011;Singh et al 2012;Yousry et al 2009;Praddhessh et al 2017;Seanego and Roland (2012); Naragani et al 2016;Zaher et al 2015). On the other hand, pyrrolo [1,2-a] pyrazine-1,4-dione obtained from marine bacterial isolates effectively inhibits S. aureus (Kiran et al 2018), more than pyrrolo [1,2-a] pyrazine-1,4dione isolated from mangrove land found that Streptomyces mangrosivoli isolate can be used as an antioxidant agent (Ser et al 2015). Linolenic acid compounds are reported to have antioxidant abilities and Stigmasterol potential as antimicrobial and anticancer agents (Subaiyyan et al 2014).…”
Section: Discussionmentioning
confidence: 99%